THE CALAMUS JAVENSIS (ARECACEAE: CALAMOIDEAE) COMPLEX IN HISTORICAL BIOGEOGRAPHIC CONTEXT - Mega Atria; Peter C van Welzen (REINWARDTIA, 2021)
ATRIA, M. & VAN WELZEN, P. C. 2021. The Calamus javensis (Arecaceae: Calamoideae) complex in historical biogeographic context.  Reinwardtia  20(1): 1−7. — Calamus javensis  is a very polymorphic species with a number of recognisable forms (of which several were once even recognized at species level). A historical biogeographic analysis showed no historical distribution pattern in the diversification of these various forms. The forms are very likely the result  of  adaptation  to  local  circumstances,  whereby more or less identical  forms  can  develop  under similar niche circumstances  in  disjunct areas,  exceptions  are  the  ‘acuminatus-polyphyllus’ form and C.  tenompokensis  that are recognisable and present in a non-disjunct area.